2022
DOI: 10.1108/cms-02-2021-0079
|View full text |Cite
|
Sign up to set email alerts
|

How does liability of origin influence cross-border acquisition completion? Evidence from Chinese firms

Abstract: Purpose The environment of international business (IB) and the capabilities of emerging market multinational enterprises (EMNEs) as well as their home countries have changed significantly, leading to some new features of liability of origin (LOR). This paper aims to extend the LOR literature by particularly focusing on the LOR of Chinese multinational enterprises (MNEs) and by taking into account the heterogeneity among industries and across individual MNEs. Design/methodology/approach Based on the stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
(300 reference statements)
0
5
0
Order By: Relevance
“…, 2012) because of the increased understanding of the host country’s business environment. Moreover, by increasing risk, distrust and information asymmetry, poor home-host political relations hinder the completion of Chinese CBMAs (Jiang et al. , 2022) and increase the transaction price paid by Chinese acquirers (Ding et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2012) because of the increased understanding of the host country’s business environment. Moreover, by increasing risk, distrust and information asymmetry, poor home-host political relations hinder the completion of Chinese CBMAs (Jiang et al. , 2022) and increase the transaction price paid by Chinese acquirers (Ding et al.…”
Section: Resultsmentioning
confidence: 99%
“…Leveraging the EMF context, in the post-M&A stage, it has been found that they tend to acquire firms in countries with close trade and economic ties (Anwar and Mughal, 2017;Buckley et al, 2012) because of the increased understanding of the host country's business environment. Moreover, by increasing risk, distrust and information asymmetry, poor home-host political relations hinder the completion of Chinese CBMAs (Jiang et al, 2022) and increase the transaction price paid by Chinese acquirers (Ding et al, 2022). However, the impact of international relations on ownership choice remains unclear.…”
Section: Home Country Factors In Cbmas Bymentioning
confidence: 99%
“…Many Chinese firms suffer from being negatively stereotyped, adversely impacting their cross-border M&As and internationalization. 91 This effect might be exacerbated if China gets more involved in its strategic partnership with Russia. Private companies from a wider range of industries may be exposed to geopolitical fallout if the line between private firms and the state becomes more blurred in China.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese firms are not unique in this regard; emerging economies are often synonymous with low-quality products and services because of their capacity deficits in technology, capital access and legal setup (Tan and Yang, 2021). The findings of Jiang et al (2022) in this special issue may be meaningful for those aiming to explore global markets and to be world-class businesses. Their research explores the liability of origin problem with the special attentions to the heterogeneity of countries, industries and firms.…”
Section: An Introduction To This Special Issuementioning
confidence: 94%